Elements of nonequilibrium statistical mechanics - Balakrishnan, V. K., 1931- (Ane Books ; CRC Press, 2008)
This book deals with the basic principles, techniques, and advances being made--both experimentally and theoretically--in the study of nonequilibrium phenomena, particularly in statistical physics, chemical physics, biological physics, complex systems, and several other areas. Accessible to senior undergraduate students and post-graduate students, this self-contained book offers a choice of topics that enables them to form a coherent picture of the subject. Coverage includes equations and formulas for calculating distribution, diffusion, and dynamic mobility under different conditions. The book concludes with a generalized Langevin equation and the power spectrum of pulse sequences.